2000
DOI: 10.1021/ic0006551
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Early-Transition-Metal Palladium Pnictides Zr3Pd4P3, Hf3Pd4P3, HfPdSb, and Nb5Pd4P4

Abstract: Several ternary palladium pnictides of the early transition metals have been prepared by arc-melting of the elemental metals and the binary pnictides ZrP, HfP, HfSb2, or NbP, and their structures have been determined by X-ray diffraction methods. The phosphides M3Pd4P3 (M = Zr, Hf) adopt a new structure type (Pearson symbol oP40), crystallizing in the orthorhombic space group Pnma with Z = 4 and unit cell parameters of a = 16.387(2), b = 3.8258(5), and c = 9.979(1) A for Zr3Pd4P3 and a = 16.340(2), b = 3.7867(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Extending our systematic studies of ternary transition metal rich pnictides, in which we have discovered the compounds M 3 Pd 4 P 3 (M = Zr, Hf), Nb 5 Pd 4 P 4 , M 3 Ni 3 Sb 4 (M = Zr, Hf), Zr 3 Pt 3 Sb 4 , and Nb 28 Ni 33.5 Sb 12.5 , we report here several members of a new family of quaternary (or pseudoquaternary) transition metal rich antimonides Nb 4 Pd 0.5 ZSb 2 (Z = Cr, Fe, Co, Ni, Si). They represent the first examples of a filled V 4 SiSb 2 -type structure, or a quaternary ordered substitutional variant of the W 5 Si 3 -type structure …”
Section: Introductionmentioning
confidence: 77%
“…Extending our systematic studies of ternary transition metal rich pnictides, in which we have discovered the compounds M 3 Pd 4 P 3 (M = Zr, Hf), Nb 5 Pd 4 P 4 , M 3 Ni 3 Sb 4 (M = Zr, Hf), Zr 3 Pt 3 Sb 4 , and Nb 28 Ni 33.5 Sb 12.5 , we report here several members of a new family of quaternary (or pseudoquaternary) transition metal rich antimonides Nb 4 Pd 0.5 ZSb 2 (Z = Cr, Fe, Co, Ni, Si). They represent the first examples of a filled V 4 SiSb 2 -type structure, or a quaternary ordered substitutional variant of the W 5 Si 3 -type structure …”
Section: Introductionmentioning
confidence: 77%
“…Current methods of preparing nanosized particles of TMPs typically employ arrested precipitation or solvothermal routes, both of which require relatively high temperatures. For the late transition metals, pioneering studies by Brock and Schaak on the synthesis of nanosized TMPs have been focused on the use of trioctylphosphine (TOP) and trioctylphosphine oxide (TOPO) at temperatures generally in the range 200–300 °C. In addition, Brock has also demonstrated that desilylation could be used to produce FeP nanoparticles at 240–300 °C. These high-temperature routes to TMPs in most cases provide the most thermodynamically stable, well-known crystalline phase of the material.…”
mentioning
confidence: 99%
“…48 No similar palladium polyhydrido cluster has been reported so that a Pd 4 P 4 moiety may be recognized only in the ternary palladium phosphide Nb 5 Pd 4 P 4 prepared by arc-melting of metallic palladium with NbP. 49 Therefore, the peculiar arrangement of four metals and four phosphorus donor atoms ascertained for 2 and 3 in both the solid and solution states has no precedent in eight-membered M 4 P 4 rings and cages, and likely its formation stands on steric reasons favored by the relatively small encumbrance exerted by the (ferrocenylmethyl)phosphine coligands.…”
Section: Resultsmentioning
confidence: 99%
“…Tetranuclear platinum compounds featuring a Pt 4 P 4 motif are extremely rare, being represented only by the spheroidal polyhydridotetraplatinum clusters [Pt 4 H 2 (P t Bu 3 ) 4 ] and Pt 4 H 8 [PPh i Pr 2 ] 4 . No similar palladium polyhydrido cluster has been reported so that a Pd 4 P 4 moiety may be recognized only in the ternary palladium phosphide Nb 5 Pd 4 P 4 prepared by arc-melting of metallic palladium with NbP …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation